DELINEATING BRITISH INDUSTRY REVOLUTION IN ENOLA HOLMES: THE CASE OF MISSING MARQUESS NOVEL BY NANCY SPRINGER - Sibarani, Philip; Woro Kasih, Elisabeth Ngestirosa Endang (Linguistics and Literature Journal, 2025)
This study aims to delineate the representation of the British Industrial Revolution in Nancy Springer’s novel “Enola Holmes: The Case of the Missing Marquess”. The research is conducted through a qualitative approach using socio-historical criticism as its theoretical framework. The Industrial Revolution, which brought massive economic, social, and political changes to Britain during the 18th and 19thcenturies, serves as a background context that shapes the narrative elements within the novel. The novel is not merely a detective story for young readers, but a literary text that embeds significant representations of industrial modernity through its characters, setting, symbols, and conflicts. The primary data of this research consist of narrative excerpts and quotations from the novel that reflect conditions such asurban expansion, technological advancement, gender oppression, and class division. The analysis focuses on how these elements areconstructed and symbolized through industrial images like trains, factories, newspapers, and coded messages and how they relate to the broader historical realities of Victorian England. The character of Enola Holmes, in particular, becomes a symbolic figure of female resistance who challenges gender roles and asserts independence in a society marked by patriarchal and industrial structures. The findings of the study indicate that Nancy Springer’s novel offers a subtle yet powerful critique of the social inequalities and ideological tensions of the Industrial Era. Enola’s journey through industrial London represents more than a personal quest; it mirrors the largerstruggles of individuals especially women and the lower class against societal systems that sought to define, confine, and control them. This research contributes to the field of literary studies by highlighting how children’s fiction can function as a vehicle for socio-political commentary and historical reflection. Keywords: class, Enola Holmes, gender roles, industrial Revolution, socio-historical criticism, symbolism, Victorian society